2001
DOI: 10.1086/318263
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Differentiation in Regions of Massive Star Formation

Abstract: We have reexamined the origin of the apparent differentiation between nitrogen-bearing molecules and complex oxygen-bearing molecules that is observed in hot molecular cores associated with massive protostars. Observations show that methanol is an ubiquitous and abundant component of protostellar ices. Recent observations suggest that ammonia may constitute an appreciable fraction of the ices toward some sources. In contrast to previous theories that suggested that N/O differentiation was caused by an anticorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
163
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(179 citation statements)
references
References 26 publications
12
163
4
Order By: Relevance
“…This could be a possible explanation for the high HCN abundance found from the absorption lines, which is an order of magnitude higher than found in the more extended Orion ridge (Bergin et al 1997). The HCN and C 2 H 2 abundances also agree well with predictions from hot core models by Rodgers & Charnley (2001). Abundances taken at a single temperature/density point from envelope models following Doty et al (2002) are in agreement with the low end of the observed range (see Table 2 and Sect.…”
Section: Abundancessupporting
confidence: 78%
See 3 more Smart Citations
“…This could be a possible explanation for the high HCN abundance found from the absorption lines, which is an order of magnitude higher than found in the more extended Orion ridge (Bergin et al 1997). The HCN and C 2 H 2 abundances also agree well with predictions from hot core models by Rodgers & Charnley (2001). Abundances taken at a single temperature/density point from envelope models following Doty et al (2002) are in agreement with the low end of the observed range (see Table 2 and Sect.…”
Section: Abundancessupporting
confidence: 78%
“…These are higher than predicted by gas-phase models at T < ∼ 200 K, which predict abundances of < ∼ 5 × 10 −8 at late times. For T > ∼ 200 K HCN and C 2 H 2 abundances of ∼10 −7 are easily produced by gas-phase models (Rodgers & Charnley 2001;Doty et al 2002). The HCN abundance is also higher than the values of ∼10 −8 derived from submillimeter observations by Blake et al (1987) and Schilke et al (1992) for the extended ridge.…”
Section: Comparison With Chemical Modelsmentioning
confidence: 75%
See 2 more Smart Citations
“…17]. The chemical model is based on the model of Rodgers & Charnley [60], and has been updated to incorporate recent laboratory measurements of the dissociative recombination channels for several ions, including CH 3 OH + 2 [44,61,62,63,64]. The initial molecular abundances in the newly-formed clump are determined by those in the interclump medium, which are themselves controlled by both (i) the chemistry in these regions, and (ii) whether the material previously passed through a dense phase.…”
Section: Chemical Modelmentioning
confidence: 99%